PRAKTIK TATO DALAM PERSPEKTIF IMAN KATOLIK: REFLEKSI TEOLOGIS DAN PASTORAL - Roida Sihombing; Andeas Mayong Acin (IN VERITATE LUX, 2025)
This study explores in depth the practice of tattooing as a bodily expression imbued with personal and spiritual meaning in contemporary human life, particularly when examined in relation to the Catholic understanding of the dignity of the human body. The body is not viewed merely as a space for individual self-expression, but as an integral dimension of the human person, created in the image and likeness of God. Employing a qualitative method through a theological and pastoral reflective approach, this study relies on a literature review of official Church documents, theological works, and relevant scholarly journal articles. The findings indicate that tattoo practices cannot be assessed in a uniform or purely normative manner, as their meaning is closely shaped by personal motivation, socio-cultural context, and their relationship to moral responsibility and faith life. From a pastoral perspective, the presence of tattoos within the life of the Church presents both challenges and opportunities for fostering more personal and contextual faith-based dialogue. This study underscores the need for a wise and compassionate pastoral attitude, enabling the Church to accompany the faithful so that tattoo practices may be understood as part of the human journey in seeking meaning and living out the Catholic faith maturely amid ongoing changes in body culture.